Synthesis of zn- al-3,4,5- trihydroxybenzoic acid – layered double hydroxide (ldh) by direct method and its controlled release activity / Siti Hafizah Aminuddin - Aminuddin, Siti Hafizah (Faculty of Applied Sciences, 2016)
Synthesis of new hybrid nanocomposite material zinc-aluminium-3,4,5-trihydroxybenzoic acid (Zn-Al-Gallic acid) was successfully attained by the direct method with a molar ratio of Zn to Al; R=4 at different concentration of 3,4,5-trihydroxybenzoic acid in the range between 0.05 M to 0.5 M. The synthesis pH is 7.0+ 0.5 and keeps in constant. The result from intercalation of gallic acid anion into zinc-aluminium-layered double hydroxide (Zn-Al-LDH) prove that size of interlayer spacing increasing from 8.8 Å in the layered double hydroxide to 9.8 Å in the Zn-Al-Gallic acid nanocomposite observed from the PXRD diffractogram. FTIR spectrum of synthesis of Zn-Al-Gallic acid nanocomposite shows the similarities of the Zn-Al-LDH and the gallic acid absorption bands which confirmed the gallic acid absorb into LDH inorganic interlayer. The percentage loading of the gallic acid results around 47.13 % (w/w) successfully intercalates into the interlayer based on the calculation and data obtained from the CHNS analysis. GA reaches equilibrium at 72 % released at 150 min so it can reach the target area efficiently.